Case Report: Time-restricted feeding improves metabolism in twins with polycystic ovary syndrome and insulin resistance - Luo, Dingyan; Tan, Zhouying; Feng, Jiaoyang; Li, Yu; Huang, Qi; Liao, Xin (Frontiers in Adolescent Medicine, 2025)
IntroductionAs the prevalence of overweight/obesity has increased, the prevalence of Polycystic ovary syndrome (PCOS) in adolescents has also increased significantly. The main features of PCOS in adolescents include menstrual irregularities and hyperandrogenism, manifested as hirsutism, acne, and/or elevated testosterone levels. Currently, the main treatment of PCOS is symptomatic supportive therapy. Lifestyle intervention remains the first-line therapeutic approach for adolescents with PCOS. We present a case study of Time-restricted feeding (TRF) intervention in 18-year-old monozygotic twins, both diagnosed with PCOS and insulin resistance (IR).MethodsThe twins underwent an 8-hour TRF intervention for 24 weeks (eating window between 8:00 a.m. and 4:00 p.m., with only water permitted during the remaining time; daily caloric intake was restricted to 1,200–1,500 kcal). Changes in waist circumference, body weight, body mass index (BMI), lipids, alanine aminotransferase (ALT), aspartate aminotransferase (AST), aspartate aminotransferase (GGT), fasting glucose (FBG), fasting insulin (FINS), glucose metabolism (glucose disposal rate, GDR), luteinizing hormone (LH), follicle stimulating hormone (FSH), LH/FSH, total testosterone (TT), sex hormone-binding globulin (SHBG), free androgen index (FAI), anti-Müllerian hormone (AMH), menstrual cycle, Ferryman—gallwey (F-G) index and Self-Rating Depression Scale (SDS) were evaluated.ResultsSignificant changes in waist circumference, body weight, BMI, FINS, FBG, ALT, AST, GGT, HDL-L, SHBG, TES, FAI, AMH, LH/FSH were found after the TRF intervention. Additionally, there was significant improvement in IR based on the hyperinsulinemic-euglycemic clamp test. Furthermore, TRF improves menstrual irregularity and hirsutism symptoms, and may also alleviate potentially depression.ConclusionThis is the first case report of an 8-hour TRF intervention in monozygotic twins with PCOS and IR, with effective control of genetic and environmental confounders. TRF improves IR and clinical symptoms in adolescents with PCOS, and these benefits are more pronounced with higher adherence to the intervention.